Surface tension, interfacial tension and contact angles of ionic liquids - Sedev, Rossen (2011)
Ionic liquids combine the properties of molten salts (they are liquids composed predominantly of ions) and organic liquids (a variety of chemical bonds and interactions are relevant). Their unique properties have attracted significant attention over the last decade. Their interfacial properties are now coming under scrutiny because (i) they are important for their performance in specific applications and also because (ii) they provide an opportunity to study diverse chemical systems under vacuum. Recent examples from the literature are used to illustrate what is currently known. The surface tension, interfacial tension and wettability of ionic liquids resemble these of polar molecular organic liquids. It is physically clear there is a relation between surface tension and molecular structure but only general trends have been identified so far. Structural studies of the free surface of ionic liquids (e.g. with surface spectroscopy) are possible and reveal unique information about the interfacial molecular orientation. The amount of empirical data available is growing rapidly and elements of systematisation are beginning to appear. © 2011 Elsevier Ltd.